Development of dengue prediction model with neural network - Cheo, Jia Jun (2022)
The aim of this project is to develop a system that could predict the Dengue outbreak. This is done by using the prediction variables such as climate and past data. Two approaches will be used to develop the prediction models, which are Artificial Neural Network (ANN) and Generalized Additive Models (GAMs). Then, the prediction accuracy of the models will be compared. All methods can handle real life input to simulate the situation of the area where we want to predict outbreak of Dengue. It is believed that the accurate prediction of dengue outbreakcan reduce the dengue case and prevent the dengue outbreak in Malaysia.